Reflexivity in Applying “Inspiration Economy” Research - Dunya Ahmed; Mohamed Buheji (International Journal of Qualitative Methods, 2018)
The overarching aim of this research is to extend and examine the way in which the inspiration economy (IE) can be applied in different contexts and countries, bearing in mind how social and cultural contexts influence the way in which research methods and fields are utilized. This is achieved through a reflexive analysis of a research study in the context of Bosnia and Herzegovina. The originality of the method focuses on the involvement of research groups in collecting and analyzing data with minimal resources and on the role of mentoring which gives group members greater ownership of the process and results/outcomes. This leads to the different researching teams building an internal drive to implement an IE case study, which was the core study of all the research studies. The study concludes with recommendations concerning the importance of involving research groups and of opening up a new path for the knowledge community. It also stresses the power of youth and research groups for the future of research in conducting and implementing research outcomes.